CrystalGrower: a generic computer program for Monte Carlo modelling of crystal growth - Hill, A.R.; Cubillas, P.; Gebbie-Rayet, J.T.; Trueman, M.; de Bruyn, N.; Harthi, Z.A.; Pooley, R.J.S.; Attfield, M.P.; Blatov, V.A.; Proserpio, D.M.; Gale, Julian; Akporiaye, D.; et al. (ROYAL SOC CHEMISTRY, 2021)
A Monte Carlo crystal growth simulation tool, CrystalGrower, is described which is able to simultaneously model both the crystal habit and nanoscopic surface topography of any crystal structure under conditions of variable supersaturation or at equilibrium. This tool has been developed in order to permit the rapid simulation of crystal surface maps generated by scanning probe microscopies in combination with overall crystal habit. As the simulation is based upon a coarse graining at the nanoscopic level features such as crystal rounding at low supersaturation or undersaturation conditions are also faithfully reproduced.CrystalGrower permits the incorporation of screw dislocations with arbitrary Burgers vectors and also the investigation of internal point defects in crystals. The effect of growth modifiers can be addressed by selective poisoning of specific growth sites. The tool is designed for those interested in understanding and controlling the outcome of crystal growth through a deeper comprehension of the key controlling experimental parameters.